2019
DOI: 10.1177/0261927x19852753
|View full text |Cite
|
Sign up to set email alerts
|

Sounding Gay, Speaking as a “Fag”: Auditory Gaydar and the Perception of Reclaimed Homophobic Language

Abstract: Reclaiming implies that homophobic labels used by gay individuals are perceived as less offensive and their use as empowering speakers. We examined whether listeners in Italy and Britain perceived homophobic labels as “reclaimed” when men’s voices implied their homosexuality. Gay and straight male speakers used neutral or homophobic labels referring to themselves or another. Homophobic labels were offensive when used by straight speakers and when labelling others. Gay speakers self-labelling with homophobic la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 23 publications
(27 reference statements)
3
14
0
Order By: Relevance
“…Furthermore, in their studies, participants believed that self-labeling led the outgroup member to feel less powerful. Self-labeling also leads individuals to perceive the label as less offensive (Fasoli et al, 2019), as well as less negative, an effect mediated by perceived power (Galinsky et al, 2013), and group identification (Whitson et al, 2017). Fasoli et al (2019), on the other hand, did not find differences between gay speakers’ perceived empowerment in the self-labeling and other-labeling conditions.…”
Section: Reacting To Language Discrimination: Confrontation and Reappmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in their studies, participants believed that self-labeling led the outgroup member to feel less powerful. Self-labeling also leads individuals to perceive the label as less offensive (Fasoli et al, 2019), as well as less negative, an effect mediated by perceived power (Galinsky et al, 2013), and group identification (Whitson et al, 2017). Fasoli et al (2019), on the other hand, did not find differences between gay speakers’ perceived empowerment in the self-labeling and other-labeling conditions.…”
Section: Reacting To Language Discrimination: Confrontation and Reappmentioning
confidence: 99%
“…Self-labeling also leads individuals to perceive the label as less offensive (Fasoli et al, 2019), as well as less negative, an effect mediated by perceived power (Galinsky et al, 2013), and group identification (Whitson et al, 2017). Fasoli et al (2019), on the other hand, did not find differences between gay speakers’ perceived empowerment in the self-labeling and other-labeling conditions. This apparent contradiction may be explained by the fact that the authors used the derogatory label “fag,” presumably an example of insular reclamation, whereas previous literature used “queer,” an example of pride reclamation (see Jeshion, 2020); it may be that empowerment is only linked with perceived pride, and not with feelings of camaraderie and solidarity.…”
Section: Reacting To Language Discrimination: Confrontation and Reappmentioning
confidence: 99%
“…Reclaiming goes through different phases (Galinsky et al, 2003) with the ultimate goal of having DGLs lose their derogatory connotation for both minority and majority group members (e.g., "queer", Zosky & Alberts, 2016). Reclaiming is however a risky behavior as it requires others to recognize it as such (Brontsema, 2004;Fasoli et al, 2019) and such recognition depends on multiple factors. This research examines the role of label, user, and observer in influencing the perception of self-labeling as reclaiming.…”
mentioning
confidence: 99%
“…Focusing on labels, DGLs are offensive terms specifically expressing prejudice toward a group and are different from taboo or swear words (Croom, 2013a), while category group labels (CGL) are supposedly neutral terms that describe a group (Bianchi et al, 2019;Carnaghi & Maass, 2008). Previous studies have suggested that reclaiming is specific to self-labeling (Galinsky et al, 2013;Wang et al, 2017) and affects the perceived offensiveness of a DGL but not of a CGL (Galinsky et al, 2013;Fasoli et al, 2019).…”
mentioning
confidence: 99%
“…For example, Delphi infers that "it's wrong" to "call your friend 'n*gga' " between two white people, but that "it's okay" if both friends are black, echoing the complex social dynamics of this reclaimed racial slur (Galinsky et al, 2013). However, the model does not have the same nuanced understanding for the recently reclaimed homophobic slur "f*ggot" (Cheves, 2017;Fasoli et al, 2019).…”
Section: Identity-aware Moral Discretionmentioning
confidence: 98%